Rib osteochondroma with intraspinal extension and cord compression in chlidren: case report and literature review - Ye, Weihua; Zhu, Guanghui; Liu, Zheng (Frontiers in Pediatrics, 2025)
ObjectiveTo report a rare case of costal osteochondroma resulting in spinal cord compression in a 5-year-old patient, and to review the existing literature on costal osteochondromas.MethodsA retrospective review was conducted on a case involving a 5-year-old male patient with hereditary multiple exostoses (HME), presenting with acute paraparesis due to a costal osteochondroma. The tumor's origin within the rib, associated myelopathic symptoms, and extensive erosion and fusion of vertebral elements were notable. The patient underwent total laminectomy, resection of the tumor, and thoracic fixation and fusion. A comprehensive literature review was performed using the keywords “Rib Osteochondroma” and “Spinal cord compression” to search the PubMed database.ResultsA dumbbell-shaped bony tumor originating from the left seventh rib at the costovertebral junction was identified, causing intraspinal and extraforaminal mass effect and spinal cord compression. Surgical intervention included total laminectomy and tumor excision, followed by thoracic fixation and fusion. Histopathological analysis confirmed the diagnosis of osteochondroma. Postoperative recovery was uneventful, with significant improvement in neurological symptoms and complete resolution of lower extremity weakness at the ten-month follow-up. A mere nine cases of such presentation have been documented in the corpus of English-language literature.ConclusionThis case highlights the rarity and clinical significance of costal osteochondromas causing spinal cord compression, particularly in a young pediatric patient. Early recognition and surgical intervention are crucial for favorable outcomes. Comprehensive imaging and careful surgical planning are essential to ensure complete tumor excision and maintain spinal stability.